Successful hepatic resection for invasive Klebsiella pneumoniae large multiloculated liver abscesses with percutaneous drainage failure: A case report - Nojima, Hiroyuki; Shimizu, Hiroaki; Murakami, Takashi; Yamazaki, Masato; Yamazaki, Kazuto; Suzuki, Seiya; Shuto, Kiyohiko; Kosugi, Chihiro; Usui, Akihiro; Koda, Keiji (Frontiers in Medicine, 2023)
Background: Invasive Klebsiella-associated liver abscesses can progress rapidly and cause severe metastatic infections such as meningitis and hydrocephalus, which are associated with high morbidity and mortality. In patients with large multiloculated liver abscesses after percutaneous drainage failure, rapid abscess diagnosis followed by hepatic resection is necessary for early recovery and to prevent severe secondary metastatic complications. Case presentation: An 84-year-old woman was transferred to our hospital with a large liver abscess and septic shock. Abdominal CT showed multiloculated liver abscesses 15 cm in diameter in the right lobe of the liver. We first performed percutaneous liver abscess drainage, and the patient was managed in the intensive care unit, as well as treatment with intravenous administration of cefozopran according to the antibiogram. Klebsiella pneumoniae with invasive infection was confirmed by a string test; the K1 serotype with the rmpA and magA genes was determined by polymerase chain reaction and Sanger sequencing. Additional percutaneous liver abscess drainage was performed due to inadequate drainage. Although the abscess had shrunk to a diameter of 8 cm after drainage in 4 weeks, she still had a high fever and chronic inflammatory condition with persistent hyper mucus discharge from five drainage tubes. To prevent prolonged hospitalization and ensure early recovery, surgical resection was chosen, and a right posterior sectionectomy of the liver, including liver abscess, was performed. The postoperative course was uneventful, with no complications, and she was discharged after 18 days. She had no signs of abscess recurrence 1 year after surgery. Conclusion: We present a case of successful hepatic resection after percutaneous drainage failure in a patient with invasive K. pneumoniae multiloculated liver abscess.